Chronic pain due to low back pain and public policies focused on the health area - Duarte, Cristiane dos Santos; Rosa, Laura Rossi; Bauduina, Eloiza Toledo; Silva, Alan Patricio da (Seven Editora, 2023)
When analyzing one of the most recurrent types of pain, low back pain is one of the most common complaints related to the musculoskeletal system and affects a large part of the population at some point in their lives. In the context of the Unified Health System (SUS), pain is a significant concern. Chronic pain can have a negative effect on individuals' lives, affecting their ability to work, perform daily activities, and enjoy a full life. Thus, this text explores the epidemiological profile of these patients, including information on prevalence, risk factors, associated comorbidities and demographic properties. Chronic low back pain is most common in people between the ages of 30 and 60. It is evident that the incidence and prevalence are higher in females and lower in males. Advanced age, obesity, sedentary lifestyle, smoking, heavy physical labor, and a family history of low back pain are factors that can increase an individual's likelihood of developing this condition. Certain occupations can increase the risk of developing chronic low back pain. Thus, in addition to the direct costs associated with health services, chronic low back pain also generates indirect costs. It is crucial to adopt effective prevention and management strategies to minimize the burden of chronic low back pain for the State, investing in health education programs inside and outside the work environment and promoting the reintegration and adequate professional rehabilitation of affected individuals, bringing benefits both to patients and to the economy in general. DOI:https://doi.org/10.56238/innovhealthknow-006